THE TEMPEST FROM COLONIAL AND POSTCOLONIAL LENS - Mohammadi, Amirmohammad (International Review of Humanities Studies, 2021)
The paper focuses on how the colonizers who in this play are Prospero and Miranda in particular, endeavor to inflict their own socio-cultural precept including their language to make the colonized fully unprotected in The Tempest as a colonial play, but eventually fail to fulfill this attempt. In addition, the high importance of learning the language of the colonizer by the colonized gets illuminated which finally contributes to Caliban so as to undermine the roots of the colonizer in the colony. This article fully evaluates affected literary works by The Tempest, the importance of transferring the colonizer’s language to the colony, and the main colonizer and his manners and attitudes towards the colonized; it also brings forth postcolonial concepts including Mimicry, Orientalism, the double consciousness of the colonized and his unhomeliness. Furthermore, it features the dirge situation of mimic men who come across a disappointing dead end from both colonizers and the colonized. After all, this article reflects on the ever-presence of ambivalence and mimicry in colonial discourse and also the vital importance of violence as an inseparable part of the decolonization.